Characterization of NF-kB-mediated inhibition of catechol-O-methyltransferase - Conrad Matthew; Wentworth Sean; Qian Li; Nackley Andrea G; Tchivileva Inna E; Diatchenko Luda B (SAGE Publishing, 2009)
Abstract Background Catechol-O-methyltransferase (COMT), an enzyme that metabolizes catecholamines, has recently been implicated in the modulation of pain. Specifically, low COMT activity is associated with heightened pain perception and development of musculoskeletal pain in humans as well as increased experimental pain sensitivity in rodents. Results We report that the proinflammatory cytokine tumor necrosis factor α (TNFα) downregulates COMT mRNA and protein in astrocytes. Examination of the distal COMT promoter (P2-COMT) reveals a putative binding site for nuclear factor κB (NF-κB), the pivotal regulator of inflammation and the target of TNFα. Cell culture assays and functional deletion analyses of the cloned P2-COMT promoter demonstrate that TNFα inhibits P2-COMT activity in astrocytes by inducing NF-κB complex recruitment to the specific κB binding site. Conclusion Collectively, our findings provide the first evidence for NF-κB-mediated inhibition of COMT expression in the central nervous system, suggesting that COMT contributes to the pathogenesis of inflammatory pain states.